PENCIPTAAN TOKOH GENDUT DALAM NASKAH TERDAMPAR KARYA SLAWOMIR MROZEK TERJEMAHAN A.KASIM AHMAD - arianggi, tiara (Tonil: Jurnal Kajian Sastra, Teater dan Sinema, 2017)
In the Terdampar sript, in an attempt to maintain the existence of reality occurs. The third character named Gendut, Sedang and Kurus trapped in a reality in it, which make existence within each and defend the truth by giving birth to an absurd incident. Actors have a device the body, then here how actors can apply in roles and different roles in order to create the appropriate character from the character select. The actor is an individual human being who has the mindset and the existence of its own, so here how an actor can be banging their existence to the character to be played  on stage. Key words: Human, Actor, absurdity, Existence